2020
DOI: 10.3389/fnsys.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-Striatal Oscillations Are Correlated to Motor Activity Levels in Both Physiological and Parkinsonian Conditions

Abstract: Moënne-Loccoz et al. Neural Oscillations and Motor Activity the operations of these neural circuits to control motor activity. Hence, biomarkers based on neural oscillations should focus on specific features, such as narrow frequency bands, to allow differentiation between parkinsonian states and physiological movementdependent circuit modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…We also found that ChI spiking is time-locked to movement onset, and tracks the animal’s stepping cycle in the 1–4 Hz delta frequency range. Studies have reported that certain neurons in the motor cortex, thalamus, and cerebellum have spikes phase locked to LFP delta oscillations 10 14 , 51 , and projections from these areas to the striatum exhibit stepping cycle-dependent activity 10 14 . Thus, the movement-dependent entrainment of cellular delta rhythms observed in ChIs likely originates from movement-related synaptic inputs.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that ChI spiking is time-locked to movement onset, and tracks the animal’s stepping cycle in the 1–4 Hz delta frequency range. Studies have reported that certain neurons in the motor cortex, thalamus, and cerebellum have spikes phase locked to LFP delta oscillations 10 14 , 51 , and projections from these areas to the striatum exhibit stepping cycle-dependent activity 10 14 . Thus, the movement-dependent entrainment of cellular delta rhythms observed in ChIs likely originates from movement-related synaptic inputs.…”
Section: Discussionmentioning
confidence: 99%
“…44 Bradykinesia in PD is currently thought to reflect a corticosubcortical network disorder implying abnormal functional connections among the fronto-basal-gangliathalamocortical motor loop and the cerebellum. [7][8][9][10]45 By contrast, parkinsonian rigidity likely arises from abnormal inputs from GPi and substantia nigra pars reticulata to the pontobulbar reticular formation, leading to hyperactive descending projections (dorsal and medial reticulospinal tracts) directed to propriospinal as well as spinal Ia and Ib interneurons. [11][12][13] This in turn results in hyperexcitability of gamma and alpha motoneurons responsible for increased muscle tone.…”
Section: Bradykinesia and Rigidity Differently Progress After Stn-dbsmentioning
confidence: 99%
“…6 However, several recent observations suggest that bradykinesia and rigidity may reflect at least partly independent mechanisms. Whereas bradykinesia would prominently reflect a network dysfunction in the corticobasal-ganglia-thalamocortical loop, [7][8][9][10] rigidity more likely arises from functional changes in specific brainstem circuits and descending neuronal pathways to the spinal cord. [11][12][13] Hence, to better clarify possible pathophysiological differences and thus disentangle bradykinesia and rigidity in people with PD, innovative ad hoc designed studies are crucially warranted.…”
mentioning
confidence: 99%
“…Brain structures Experimentally reported frequency shifts/differences Gamma (∼30-100Hz) Neocortex Hippocampus (Traub et al, 1996;Gregoriou et al, 2009;Lima et al, 2010;Ray and Maunsell, 2010;Ahmed and Mehta, 2012;Bosman et al, 2012;Jia et al, 2013;Roberts et al, 2013;van Pelt and Fries, 2013;Lowet et al, 2017) Beta (∼15-35Hz) Neocortex Basal ganglia (Salmelin and Hari, 1994;Neuper and Pfurtscheller, 2001;Kilavik et al, 2012;Lundqvist et al, 2016;Canessa et al, 2020;Moënne-Loccoz et al, 2020) Alpha (∼8-12Hz) Neocortex Thalamus (Haegens et al, 2014;Zhang et al, 2018;Green et al, 2022;Sato, 2022) Theta (∼4-10Hz) Neocortex Hippocampus (Giocomo et al, 2007;Goutagny et al, 2009;Axmacher et al, 2010;Patel et al, 2012;Zhang and Jacobs, 2015;Zhang et al, 2018) Delta (∼1-4Hz)…”
Section: Frequency-bandsmentioning
confidence: 99%